2022
DOI: 10.1002/ecm.1507
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from a long‐term irrigation experiment in a dry Scots pine forest: Impacts on traits and functioning

Abstract: Climate change exposes ecosystems to strong and rapid changes in their environmental boundary conditions mainly due to the altered temperature and precipitation patterns. It is still poorly understood how fast interlinked ecosystem processes respond to altered environmental conditions, if these responses occur gradually or suddenly when thresholds are exceeded, and if the patterns of the responses will reach a stable state. We conducted an irrigation experiment in the Pfynwald, Switzerland from 2003-2018. A na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 105 publications
1
26
0
Order By: Relevance
“…In a Scots pine-dominated fore t i o e of witzer a d' drie t areas, we conducted leaf-level gas exchange measurements in a long-term irrigation experiment covering multiple years. Scots pine in this region is growing at the dry edge of its distribution, pushing the species to be highly drought-selected (Bose et al, 2022). Previous studies within this long-term irrigation experiment showed significant structural adjustments of the trees in response to long-term irrigation, in the form of increased leaf area and growth (Fig.…”
Section: Introductionmentioning
confidence: 83%
“…In a Scots pine-dominated fore t i o e of witzer a d' drie t areas, we conducted leaf-level gas exchange measurements in a long-term irrigation experiment covering multiple years. Scots pine in this region is growing at the dry edge of its distribution, pushing the species to be highly drought-selected (Bose et al, 2022). Previous studies within this long-term irrigation experiment showed significant structural adjustments of the trees in response to long-term irrigation, in the form of increased leaf area and growth (Fig.…”
Section: Introductionmentioning
confidence: 83%
“…The study was set up within the irrigation experiment initiated in 2003 by the Swiss Federal Research Institute for Forest, Snow, and Landscape Research WSL [37] (Fig 1), targeted at obtaining a high spatial variability in soil microclimatic conditions. Every year between April and October, half of the plots (irrigation treatment) were irrigated by a sprinkler system providing an additional 700 mm of water annually, and the other half served as control.…”
Section: Study Sitementioning
confidence: 99%
“…Intriguingly, there is evidence of this relationship between OCS and ecosystem acclimation: in a long‐term grassland irrigation experiment, which was not included in our data set, the long‐term increased precipitation treatment had the highest respiration rates (higher than short‐term increased precipitation) and increased soil labile C content (Broderick et al., 2022). Additionally, in a dry Scots pine forest irrigated for 17 years, tree responses typically took 4 years to reach a peak value and then stabilized or decreased (Bose et al., 2022). These responses included increased belowground C inputs.…”
Section: Discussionmentioning
confidence: 99%